2023
DOI: 10.1080/08989621.2023.2189010
|View full text |Cite
|
Sign up to set email alerts
|

Why research integrity matters and how it can be improved

Abstract: Scholars need to be able to trust each other, because otherwise they cannot collaborate and use each other's findings. Similarly trust is essential for research to be applied for individuals, society or the natural environment. The trustworthiness is threatened when researchers engage in questionable research practices or worse. By adopting open science practices, research becomes transparent and accountable. Only

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…7,38 Further, journal editors and publishers have a responsibility to uphold integrity by ensuring that they only publish research that has been conducted in accordance with internationally accepted guidelines. 39 To achieve this, they should routinely screen manuscripts for integrity issues, 40 and we support arguments to require sharing of raw data prior to publication. 10,31 Among journal readers and reviewers, a healthy scepticism is also encouraged; while publications were commonly accepted as truth in the past, as Moore et al argue “the biggest mistake of all, then, is taking evidence on trust and without checking it.” 41…”
Section: Discussionmentioning
confidence: 95%
“…7,38 Further, journal editors and publishers have a responsibility to uphold integrity by ensuring that they only publish research that has been conducted in accordance with internationally accepted guidelines. 39 To achieve this, they should routinely screen manuscripts for integrity issues, 40 and we support arguments to require sharing of raw data prior to publication. 10,31 Among journal readers and reviewers, a healthy scepticism is also encouraged; while publications were commonly accepted as truth in the past, as Moore et al argue “the biggest mistake of all, then, is taking evidence on trust and without checking it.” 41…”
Section: Discussionmentioning
confidence: 95%
“…Regardless of whether humans or animals are recruited as participants in a research endeavour, researchers must conform to a set of agreed-upon practices that communicate the integrity of the published work. Research integrity gains importance within a research community by allowing its members to trust and build on previous work while also developing confidence in their scholarly outputs within society (Bouter, 2023 ). Trust in the research system is thus a result of research integrity.…”
Section: Research Integritymentioning
confidence: 99%
“…Furthermore, their variation across disciplines and cultures leads to a more significant variation in regulatory responses. Research documenting the frequency of research misconduct provides different numbers but generally agrees that its prevalence among researchers deserves careful attention (Bouter, 2023 ; Fanelli & Tregenza, 2009 ; Reisig et al, 2020 ).…”
Section: Research Integritymentioning
confidence: 99%
“…There is growing consensus that preregistration facilitates transparent, credible, and reproducible research ( [1]; for critical comments see, e.g., [6,7]). Entertaining open methods such as preregistration, but also sharing code and data, are part of a wider range of responsible research practices (RRPs), which collectively aim at optimizing the validity and trustworthiness of research (e.g., [8,9]). RRPs also include, for example, careful data management, accurate documentation of all research steps and decisions, appropriately acknowledging other people's work and ideas, and correcting errors if there are reasons to do so [10].…”
Section: Findings From the Abstracts Accepted For The 7th World Confe...mentioning
confidence: 99%
“…However, it is also recognized that researchers often experience various barriers to preregister their study (e.g., [3,12,13]. These barriers may, for example, include perceived bureaucratic burden, In recent years, several studies have examined the extent to which published studies were preregistered [9,12,14,15]. These studies reported a substantial increase of preregistrations, at least as measured by the absolute number of preregistered studies in, for example, the OSF.…”
Section: Findings From the Abstracts Accepted For The 7th World Confe...mentioning
confidence: 99%